Application Culinary Decision Support System in Kudus City with Weighted Product Method Based on Mobile Phone - Anindya Khrisna Wardhani; Erba Lutfina (Journal of Computer Science and Engineering (JCSE), 2020)
Abstract: Along with the number of restaurants located in the city of Kudus, making a problem for a consumer or tourists who want to choose a restaurant. This can even take a lot of time because consumers are faced with the many choices of restaurants. Therefore, a decision support system is needed to assist consumers or tourists in choosing a culinary place. In determining the selection of culinary places in the city of Kudus, using the Weighted Product method to determine the culinary place with several criteria: the number of menus, the average price, wifi, and corner charger. The culinary site selection system with weighted product method is implemented in the mobile phone-based system. The mobile phone application is made to facilitate the admin and user choose culinary or restaurant with the process used in determining the culinary place in the city of Kudus by using criteria inputted by the user. This app is also in add google maps, so direct users can knowing location culinary location or restaurant that has become his choice.Abstrak: Seiring dengan banyaknya restoran yang berlokasi di kota Kudus, membuat masalah bagi konsumen atau wisatawan yang ingin memilih restoran. Ini bahkan dapat mengambil banyak waktu karena konsumen dihadapkan pada banyak pilihan restoran. Oleh karena itu, diperlukan sistem pendukung keputusan untuk membantu konsumen atau wisatawan dalam memilih tempat kuliner. Dalam menentukan pemilihan tempat kuliner di kota Kudus, menggunakan metode Weighted Product untuk menentukan tempat kuliner dengan beberapa kriteria: jumlah menu, harga rata-rata, wifi, dan tempat charger. Sistem pemilihan lokasi kuliner dengan metode weighted product diimplementasikan dalam sistem berbasis ponsel. Aplikasi ponsel dibuat untuk memudahkan admin dan pengguna memilih kuliner atau restoran dengan proses yang digunakan dalam menentukan tempat kuliner di kota Kudus dengan menggunakan kriteria yang dimasukkan oleh pengguna. Aplikasi ini juga di tambahkan google maps, sehingga pengguna langsung bisa mengetahui lokasi lokasi kuliner atau restoran yang sudah menjadi pilihannya.